Synthesis, Optimization, Antifungal Activity, Selectivity, and CYP51 Binding of New 2-Aryl-3-azolyl-1-indolyl-propan-2-ols - Nicolas Lebouvier; Fabrice Pagniez; Young Min Na; Da Shi; Patricia Pinson; Mathieu Marchivie; Jean Guillon; Tarek Hakki; Rita Bernhardt; Sook Wah Yee; Claire Simons; Marie-Pierre Lézé; et al. (MDPI AG, 2020)
A series of 2-aryl-3-azolyl-1-indolyl-propan-2-ols was designed as new analogs of fluconazole (FLC) by replacing one of its two triazole moieties by an indole scaffold. Two different chemical approaches were then developed. The first one, in seven steps, involved the synthesis of the key intermediate 1-(1H-benzotriazol-1-yl)methyl-1H-indole and the final opening of oxiranes by imidazole or 1H-1,2,4-triazole. The second route allowed access to the target compounds in only three steps, this time with the ring opening by indole and analogs. Twenty azole derivatives were tested against Candida albicans and other Candida species. The enantiomers of the best anti-Candida compound, 2-(2,4-dichlorophenyl)-3-(1H-indol-1-yl)-1-(1H-1,2,4-triazol-1-yl)-propan-2-ol (8g), were analyzed by X-ray diffraction to determine their absolute configuration. The (−)-8g enantiomer (Minimum inhibitory concentration (MIC) = IC80 = 0.000256 µg/mL on C. albicans CA98001) was found with the S-absolute configuration. In contrast the (+)-8g enantiomer was found with the R-absolute configuration (MIC = 0.023 µg/mL on C. albicans CA98001). By comparison, the MIC value for FLC was determined as 0.020 µg/mL for the same clinical isolate. Additionally, molecular docking calculations and molecular dynamics simulations were carried out using a crystal structure of Candida albicans lanosterol 14α-demethylase (CaCYP51). The (−)-(S)-8g enantiomer aligned with the positioning of posaconazole within both the heme and access channel binding sites, which was consistent with its biological results. All target compounds have been also studied against human fetal lung fibroblast (MRC-5) cells. Finally, the selectivity of four compounds on a panel of human P450-dependent enzymes (CYP19, CYP17, CYP26A1, CYP11B1, and CYP11B2) was investigated.